Opportunistic coinfection with Pneumocystis jirovecii and Coccidioides immitis associated with idelalisib treatment in a patient with chronic lymphocytic leukaemia. Issue 4 (29th April 2020) - Ward, Lindsey M; Peluso, Michael J; Budak, Jehan Z; Elicker, Brett M; Chin-Hong, Peter V; Lampiris, Harry; Mulliken, Jennifer S
Abstract : We describe a case of opportunistic coinfections with Coccidioides immitis and Pneumocystis jirovecii following treatment with idelalisib, a phosphoinositide 3-kinase inhibitor, for chronic lymphocytic leukaemia. This is the first case of pulmonary coccidioidomycosis reported in association with idelalisib. We review challenges related to diagnosis of opportunistic infections in this context. This report illustrates (1) the uncommon occurrence of two opportunistic infections concurrently or in rapid succession, (2) the importance of maintaining a broad differential diagnosis in the setting of an atypical imaging finding, slow clinical response or when immunomodulatory drugs are used, and (3) the challenges associated with non-invasive serological testing in individuals with haematological malignancy on immunomodulatory therapy.